2020
DOI: 10.1002/rev3.3242
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of predictors of teacher self‐efficacy in student engagement, instruction and classroom management in Nordic, Anglo‐Saxon and East and South‐East Asian countries

Abstract: Going beyond previous studies, we investigated differential effects of teacher self‐efficacy (TSE) across the three basic dimensions of educational equality in student engagement, instructional strategies and classroom management in East and South‐East Asian, Anglo‐Saxon and Nordic country clusters in a cross‐cultural analysis. It was found that all three domains of TSE show different patterns of associations in relation to teacher, classroom, principal and school predictors across the three country clusters. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 88 publications
2
6
0
Order By: Relevance
“…This suggests that the teachers' roles are more important than the book itself. This also seemed to align with Fackler et al's (2021) study, which highlights the high respect for teachers' roles and responsibilities in East and Southeast Asian countries.…”
Section: Findings and Discussionsupporting
confidence: 84%
“…This suggests that the teachers' roles are more important than the book itself. This also seemed to align with Fackler et al's (2021) study, which highlights the high respect for teachers' roles and responsibilities in East and Southeast Asian countries.…”
Section: Findings and Discussionsupporting
confidence: 84%
“…Studies indicate that both teachers' general ( Holzberger et al, 2013 ; Praetorius et al, 2017 ) and task-specific teacher self-efficacy, including self-efficacy for instructional strategies ( Lazarides & Schiefele, 2021 ), self-efficacy for classroom management ( Dicke et al, 2014 ; Lazarides et al, 2020 ), and self-efficacy for student engagement ( Fackler et al, 2021 ), positively relate to indicators of effective teaching in in-service teachers. Analysis of data from the 2018 Teaching and Learning International Survey (TALIS 2018; OECD, 2019 ) found that teachers reporting higher teacher self-efficacy also reported using higher quality teaching strategies ( Holzberger & Prestele, 2021 ), which in turn could lead to greater student motivation and learning through their effects on students’ perceptions of teaching quality ( Lauermann & Berger, 2021 ).…”
Section: Teacher Self-efficacy: Definition and Importance For Student...mentioning
confidence: 99%
“…In line with Bandura’s (1986) work, we expect the teacher’s sense of efficacy for engaging students to prompt the teacher to create an emotionally supportive learning environment. Accordingly, recent research has confirmed associations between teacher self-efficacy for student engagement and teacher-reported social classroom climate (Fackler et al, 2021), a construct that also includes aspects of emotional support, such as creating a pleasant atmosphere in class (OECD, 2014). In line with the SEVT-based assumptions that socializers’ value beliefs closely relate to their behaviors, which then relate to student value (Dicke et al, 2021; Eccles et al, 1998), we theorize that teachers who value teaching (here: teachers’ educational interest) contribute to students’ interest by providing emotionally supportive learning.…”
Section: Indirect Effects From Teacher Motivational Beliefs To Studen...mentioning
confidence: 99%